Construcción de una guía de densidad para Pinus cooperi var. ornelasi con base en la clase de copa en Durango, México - Márquez-Linares, Marco A.; Alvarez-Zagoya, Rebeca (Instituto de Ecología, A.C., 1995)
The objective of the present study is to construct a density management diagram for Pinus cooperi var ornelasi stands in the state of Durango, México. The resulting diagram, based on different crown classes, was constructed for the existing even-aged trees. The line of crown closure reached a Reineke stand density index of 310.31, the line for dominant crow n trees reached 658.62, the line for intermediate crown trees was 720.18, and the line for suppressed crown trees was 1007.05 SDi. These lines indicate possible density ranges within which a even-aged Pinus cooperi stand could be managed. The methodology used yielded results similar to those found for other pine species in Mexico.